Increased Efficiency of Phorbol Ester-Induced Lytic Reactivation of Kaposi's Sarcoma-Associated Herpesvirus during S Phase - McAllister, Shane C. (American Society for Microbiology, 2005)
Expression of Kaposi's sarcoma-associated herpesvirus (KSHV) lytic genes is thought to be essential for the establishment and progression of KSHV-induced diseases. The inefficiency of lytic reactivation in various in vitro systems hampers the study of lytic genes in the context of whole virus. We report here increased expression of KSHV lytic genes and increased release of progeny virus when synchronized cultures of body cavity-based lymphoma-1 cells are treated with a phorbol ester during S phase of the cell cycle.